Stochomys longicaudatus (Rodentia: Muridae). (9th August 2019) - Uebbing, Severin
Abstract: Stochomys longicaudatus (Tullberg, 1893) is a monotypic African murid rodent called the target rat because long bristle-like hairs in its fur resemble arrows stuck into a target, giving it a unique appearance. Although occurring in comparatively low densities, it is widely spread throughout the lowland rainforests of equatorial western and central Africa. Inhabiting dense understory vegetation, it is a secretive and perhaps nomadic species and little is known about its behavior. S. longicaudatus is herbivorous, climbs well and often, and builds nests from shredded grass. The International Union for Conservation of Nature and Natural Resources classifies it as a species of "Least Concern."